Comparative analysis of the Mexican and Colombian health system - García Hernández, Héctor; Esquer Bojorquez, David (Población y Salud en Mesoamérica, 2024)
Introduction: The model, proposed by Federico Tobar, for the comparison between health systems mentions the review of three different dimensions: health policies, epidemiological situation, and health system, to delve into similarities and differences that exist between systems from several countries. Proposal: The health systems of Mexico and Colombia share characteristics and reforms that make them similar, however, an analysis framework is required to make a structured comparison. Argument: The reforms in the health policies of Mexico and Colombia generated a fragmented health system that serves different types of populations, in the case of Mexico it is based on social security, and in Colombia on structured pluralism or regulated market; in both cases, it has not been possible to reverse this situation. The health situation in both countries is similar, dominated by a decrease in infectious diseases and an increase in chronic-degenerative diseases, as well as the appearance of health social problems (like homicides). Finally, there are multiple components in both health systems. This generates a scenario with several subsystems in the case of Mexico and different actors in Colombia. Conclusion: Both health systems are fragmented, with policies that try to increase their coverage. They have comparable epidemiological profiles, which suggests that they face related needs within the health system itself. A pending issue for both is the equity in the services which has been unequal.